Visual analysis of the research frontiers, hotspots and trends of exercise therapy intervention in tumor-related sleep-wake disorders - Han, Jilei; Zhang, Jiachen; Zhang, Litao; Guo, Juan; Peng, Xitao; Ying, Chenlin; Li, Zhiqing; Li, Mu; Chang, Lihua; Zhang, Yani (Frontiers in Oncology, 2024)
Objective: To systematically understand the research frontiers, hotspots and development trends of exercise therapy in the intervention of tumor-related sleep-wake disorders, and to provide scientific basis for follow-up research. Methods: Downloaded the original research papers on February 26, 2024, from the Web of Science core collection database, on tumor-associated sleep-wake disorders. The data that met the inclusion criteria were imported into the Bibliometric Analysis Platform (http://biblimetric.com), CiteSpace 6.3.R1 and VOSviwer1.6.20 software for visual analysis, and imported into Excel2021. Scientometric analysis was performed with Oringin2021 and PyCharm Community Edition 2022.1.3. Results: A total of 512 original research papers on tumor-related sleep-wake disorders were obtained. The most influential countries in the subject area are the United States, Spain and German, the institutions are the